2007
DOI: 10.2193/2006-389
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Analysis of Bobcat Habitat in the Northern Lower Peninsula of Michigan

Abstract: Controversy over bobcat (Lynx rufus) management in the northern Lower Peninsula of Michigan (NLP), USA, stimulated a need for information on the distribution of Michigan bobcats. From March 2003 to October 2004, we conducted a radiotelemetry and scentstation survey study of bobcats in the NLP. We developed a spatial model to predict bobcat distribution throughout the NLP based on bobcat area requirements, habitat and landscape variables derived from remotely sensed land‐cover data, and a multivariate distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 23 publications
4
21
0
Order By: Relevance
“…Nearly all studies of bobcat habitat relationships have concluded that bobcat presence and abundance is influenced by the distribution and characteristics of forested habitat (Woolf et al 2002, Preuss and Gehring 2007), especially at the local scale (Lovallo et al 2001, Constible et al 2006, Tucker et al 2008). However, our analyses and modeling highlight that the quantity and configuration of other habitats, especially perennial grassland cover in association with woodlands, predicted relative abundance of Iowa bobcats at the county scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nearly all studies of bobcat habitat relationships have concluded that bobcat presence and abundance is influenced by the distribution and characteristics of forested habitat (Woolf et al 2002, Preuss and Gehring 2007), especially at the local scale (Lovallo et al 2001, Constible et al 2006, Tucker et al 2008). However, our analyses and modeling highlight that the quantity and configuration of other habitats, especially perennial grassland cover in association with woodlands, predicted relative abundance of Iowa bobcats at the county scale.…”
Section: Discussionmentioning
confidence: 99%
“…Given the various habitat factors that have been identified from region to region (Larivière and Walton 1997, Anderson and Lovallo 2003), development of region‐specific habitat models has been a goal of bobcat conservation and management (Bluett et al 2001). Many habitat models have been built based on data collected in landscapes that were primarily forested (e.g., Maine, Litvaitis et al 1986; Wisconsin, Lovallo and Anderson 1996; Mississippi, Constible et al 2006; Michigan, Preuss and Gehring 2007). On a statewide basis, the landscape of Illinois where Woolf et al (2002) developed a bobcat habitat model is most similar to Iowa.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We considered distance to roads in all periods for each species because roads influence carnivore space use and resource selection (Roy and Dorrance 1985, Hellgren et al 1991, Lovallo and Anderson 1996, Wydeven et al 2001. We examined the effect of land cover edges on carnivore resource acquisition (Ries et al 2004, Preuss andGehring 2007) by including distance to land cover edge in all periods for all carnivores. We considered distance to grassland or pasture in black bear models for all periods because grasses are an important food source for black bears when other food sources are lacking, particularly in spring (Pelton 2003).…”
Section: Modelingmentioning
confidence: 99%
“…Preferred bobcat habitats such as forest (Hall and Newsom 1976, Rucker et al 1989, Lovallo and Anderson 1996, Nielsen 2000 and grassland (Kamler and Gipson 2000) occur in a fragmented mosaic of patches and corridors in Iowa (Kane et al 2002) that may affect bobcats by limiting their movements, altering home range boundaries, and modifying habitat selection patterns (Sunquist and Sunquist 2001). Previous studies of bobcat habitat selection have been conducted in areas such as Wisconsin (Lovallo and Anderson 1996), Michigan (Preuss and Gehring 2007), and Mississippi (Chamberlain et al 2003), USA, where large, continuous areas of forest are widespread, although Kamler and Gipson (2000) showed that bobcats selected grassland over forest in Kansas, USA. In recent decades the enrollment of land into the Conservation Reserve Program (CRP) may have led to increases in the amount of potential habitat available to bobcats and their prey, so it is reasonable to suggest that CRP lands could be important to the population ecology of bobcats in Midwestern landscapes.…”
mentioning
confidence: 99%